ANALISIS MISKONSEPSI SISWA DALAM MENYELESAIKAN PERMASALAHAN PERSAMAAN KUADRAT SATU VARIABEL DITINJAU DARI PERBEDAAN GENDER - Ikram, Risnul Lailatul; Suharto, S; Setiawani, Susi (Kadikma, 2018)
This study aims to describe a gender-based of students' misconceptions in contextual solving one variable quadratic equations. The research subjects were 6 students consisting of 3 students for each gender in Argopuro Panti High School. Data collection methods used are tests and interviews. Based on data analysis, the results of the study show that there are several misconceptions experienced by students namely misconception of notation, square root misconception, misconception of chancellor law and / or multiplication identity, misconception of side length comparisons, and constructive misconceptions. Based on the 3 subjects of each gender it can be concluded that male students experience more misconceptions at the stage of carrying out the plan, namely the chancellor's law misconceptions and or multiplication of identity rules, misconceptions in side length comparisons, constructional misconceptions, and notation misconceptions, while female students experience more misconceptions at the stage of revisiting namely square root misconceptions, misconceptions of side length comparisons, constructional misconceptions. Misconceptions that occur in both genders are misconceptions of notation, misconceptions in comparison of side lengths and misconceptions about building space. The teacher must be able to distinguish students who experience errors and misconceptions, because if the student is classified as a student of misconception, then the teacher must be able to deal with it immediately and precisely, because it can affect the mindset and learning outcomes of students.